A rare case of acute abdomen in an elderly patient: Jejunal diverticulum perforation - Uludag, Server Sezgin; Gures, Nazim; Askar, Ahmet; Kucuk, Omer; Zengin, Abdullah Kagan; Ozcelik, Mehmet Faik (Annals of Medical Research, 2021)
Jejunal diverticulosis is rare condition that commonly seen in elderly patient. The majority of cases are asymptomatic; however nonspecific abdominal symptoms like abdominal pain, nausea and diarrhea can be seen. Diverticulum perforation leads to generalized or localized peritonitis which may lead to emergency surgical intervention. Diagnosis of Jejunal diverticulosis is often difficult and it is commonly diagnosed incidentally by screening for other purposes. Jejunal diverticulosis is false diverticulum and is believed that Jejunal diverticulosis arises from herniation of the intestinal mucosa and submucosa without a muscle layer. In this report an 88-year-old male patient was admitted to the emergency department with abdominal pain. In abdominal computed tomography (CT) free gas and fluid were observed in the perihepatic area and between the jejunal loops. The patient was taken to emergency operation. During exploration, multiple diverticules were noted in the jejunum. Microperforation area was seen in one of the diverticula. Approximately 50 cm of jejunal segment with diverticulum was resected. The patient was discharged on the sixth day without any remarkable complications.